The Influence of Body Mass Index on Outcomes After Hip Arthroscopy for Femoroacetabular Impingement Syndrome: Five-Year Results in 140 Patients. Issue 1 (January 2021) - Parvaresh, Kevin; Rasio, Jonathan P.; Wichman, Daniel; Chahla, Jorge; Nho, Shane J.
Background: Significant short-term improvements in function and pain after arthroscopic management of femoroacetabular impingement syndrome (FAIS) have been demonstrated regardless of mass index (BMI). No studies have reported the influence of obesity on mid- to long-term outcomes. Purpose: To evaluate the effect of BMI class on 5-year patient outcomes after arthroscopic treatment of FAIS. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of a prospective database was performed to identify patients who underwent arthroscopic treatment for FAIS. A matched-pair analysis for age and sex was performed in a 1:1:2:3 fashion for morbidly obese (BMI ≥35), obese (BMI = 30-34.9), overweight (BMI = 25-29.9), and normal weight (BMI = 18.5-24.9) patients, respectively. Patient characteristics, imaging, Hip Outcome Score Activities of Daily Living (HOS-ADL) and Sports Subscale (HOS-SS) scores, modified Harris Hip Score (mHHS), and pain scores were recorded preoperatively, with the same outcome scores recorded at 5 years postoperatively, along with satisfaction scores. Standardized modern hip arthroscopy, with labral repair, acetabuloplasty, femoroplasty, and capsular plication followed by formalized rehabilitation, was performed for all patients. Absolute outcomes along with change in outcomes were assessed between BMI groups. A between-group analysis was also conducted evaluating achievement of the minimal clinically important difference (MCID), patient acceptable symptomatic state (PASS), and substantial clinical benefit (SCB) for any outcome score. A multivariable analysis was additionally included to evaluate outcomes adjusting for known confounding variables. Results: A total of 140 patients with mean follow-up of 62.1 ± 6.5 months were identified: 20 morbidly obese, 20 obese, 40 overweight, and 60 normal weight. There were significant improvements for HOS-ADL, HOS-SS, and mHHS scores in the normal (all P < .0001) and overweight groups (all P < .0001), mHHS in the obese group ( P = .0275), and no significant improvement in functional scores in the morbidly obese group ( P > .05). Compared with normal controls, multivariable analysis, adjusting for confounders, showed similar improvement in HOS-ADL for patients in the overweight and obese groups, HOS-SS for patients in the overweight group, and mHHS for patients in the overweight and obese groups (all P > .05). All groups showed significant improvement in pain scores (all P < .01) that were not significantly different between groups in multivariable analysis (all P > .05). Obese BMI was associated with a 54.9-point decrease in 5-year HOS-SS, and morbidly obese BMI was associated with a 27.3, 35.0, and 23.7-point decrease in 5-year HOS-ADL, HOS-SS, and mHHS, respectively (all P < .05). Regarding surgical benefit in comparison with normal weight patients, patients in the overweight and obese groups were as likely to achieve MCID (reciprocal odds ratio [ROR]: 1.5 and 1.2, respectively, both P > .05), but patients in the morbidly obese group were not. All groups were significantly less likely than the normal weight group to achieve PASS (ROR: overweight 5.2, obese 14.1, morbidly obese 13.0; all P < .05) and SCB (ROR: overweight 3.9, obese 7.8, morbidly obese 20.3; all P < .05). Conclusion: There were significant improvements in at least 1 outcome score across all BMI groups with arthroscopic treatment of FAIS. While the normal weight patients demonstrated universal improvement in all patient-reported outcomes and significantly greater likelihood of achieving PASS and SCB, the higher BMI groups still demonstrated significant improvement in function and pain, except for the morbidly obese group. Patients with morbid obesity demonstrated long-term pain improvement, although they did not experience functional improvement.